Determination of Abraham model solute descriptors for o-acetoacetanisidide based on experimental solubility data in organic mono-solvents. (4th July 2019) - Lee, Grace; Che, Melanie; Qian, Ellen; Wang, Lainey; Gupta, Avi; Neal, Reese; Yue, David; Downs, Samantha; Mayes, Tiffany; Rose, Olivia; Acree, William E.; Abraham, Michael H.
ABSTRACT: Spectrophotometric methods were used to measure the mole fraction solubility of o-acetoacetanisidide dissolved in 13 alcohol solvents (ethanol, 1-propanol, 1-butanol, 1-pentanol, 1-hexanol, 1-heptanol, 2-propanol, 2-butanol, 2-methyl-1-propanol, 2-methyl-2-propanol, 2-methyl-2-butanol, 3-methyl-1-butanol and 4-methyl-2-pentanol), in 3 dialkyl ether solvents (diisopropyl ether, dibutyl ether and methyl tert -butyl ether), in 6 alkyl alkanoate solvents (methyl acetate, ethyl acetate, propyl acetate, butyl acetate, pentyl acetate and methyl butyrate) and in 1 alkanenitrile solvent (propanenitrile) at 298.15 K. Solute descriptors were calculated for o-acetoacetanisidide by analysing the measured solubility data in accordance with the Abraham solvation parameter model. The calculated solute descriptors describe the observed solubility data to within 0.099 log units.